Implementing interactive multiple criteria decision methods in public policy - Wallenius, Hannele (1991)
The focus of this study is on implementing several state-of-the-art interactive multiple criteria decision-making approaches to structuring and solving problems in the public policy domain. The multiple objective linear programming research framework was adopted and its suitability for analyzing problems in public policy was investigated. The following four problems were studied: a macroeconomic policy problem, a problem of emergency management, an environmental policy problem, and an agricultural income policy problem. Each case represented an important real-world decision problem. Each case also involved close contacts with decision-makers and/or their staff in order to capture all relevant issues in the mathematical formulation of the underlying problem, and to test the research framework and the interactive solution strategy in particular. Since the interactive solution strategy used involves a decisionmaker and his/her value judgements in the formulation and solution process, its usefulness could not be demonstrated theoretically without empirical testing and applications. The purpose was to learn useful lessons about the problems and issues involved in implementing management science models and methods in practice. Lessons learned deal with the modelling of public policy, the pros and cons of the interactive solution strategy, and the problems of implementing the interactive solution strategy in practice.